Questions paysagères et paysagistes dans les agences d’urbanisme - Isabelle Estienne (Territoire en Mouvement, 2007)
By the end of the 1960s, the Lille-Roubaix-Tourcoing conurbation had been designated as a « métropole d’équilibre » (a balanced Metropolitan area). The number of actors in the planning sector was increasing, working in different organizations which were often in competition not only in their missions but also in their field of competency, these include: AUAM (The Urban Planning and Development Office of Lille Métropole), OREAM Nord (a metropolitan area development study organisation), GEP (a group for study and programme planning), Atelier du Centre Directionnel (a workshop for planning a directional centre), EPALE (a public study organisation for the planning of the Lille East new Town). The creation of these organisations is the result of the will to define the future of large territories: As from 1968, the mission of the Oream-nord was a global study of the whole region. This period is also defined by the preoccupation of French society with the quality of their living environment, by the consideration of different aspects, notably the environmental and ecological factors. The presence of a landscape architect in the team was a decisive factor in placing these questions central to the Oream-Nord thinking, thus giving considerable importance to the question of landscaping. The ideas of Jean Challet appear today to be astonishingly contemporary. He proposed that a system of basins be implemented, to protect the catchment area and for the self purification of polluted water, having a dual recreational and environmental purpose. His unrealised project of a park on the banks of the Deûle, were updated in 2002, in the Schéma Directeur de développement et d’urbanisme (master plan). Other OREAM have benefited from the input of Landscape architects – Jacques Sgard for the OREAM of Marseille and the OREAM of Lorraine, Pierre Dauvergne for the Loire Moyenne and Michel Viollet at Saint-Nazaire. What was the place of this profession in the first urban planning offices? The two examples of Lille (AUAM) and Dunkerque (AGUR) serve to analyse how the organisations of the 1970s take account of the questions of landscape quality.